Preferensi Konsumen dalam Memilih Metode Pembayaran Digital (Studi Kasus Pada Usaha Rumahan Pengolahan Hasil Laut di Desa Sentang Kec.Teluk Mengkudu Kabupaten Serdang Bedagai, Sumatera Utara) - Meliza*, Juli; Hastalona, Dina (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
Digital payment methods have experienced significant development, especially for small and medium businesses. The development of digital financial transformation in SMEs has become an interesting topic in recent research. Adoption of digital finance innovations can lead to long-term performance improvements in SMEs. This study aims to analyze the factors of Social Media Influencers, Company Brand Image, Promotional Benefits, Financial Technology Knowledge, Perceived Convenience Use, and Perception of Risk to interest in using digital payments in seafood processing home-based businesses in Sentang Village, Teluk Mengkudu District, Serdang Bedagai Regency, North Sumatra. Quantitative research method with analytical descriptive analysis techniques. The results of this study indicate that social media influencers and perceived risk have a negative and insignificant effect. Meanwhile, Promotional benefits, Fintech knowledge, Perceived usefulness, have a positive and significant effect. It is hoped that by understanding the factors that influence consumer choice, stakeholders can develop strategies to increase the adoption and use of digital payment systems, increase customer satisfaction, and drive economic growth.